Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan Pada Usaha UMKM Pengolahan Perikanan - Ian Nurpatria Suryawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to obtain information on the influence of the selection system, training on employee performance mediated by communication in fisheries processing MSMEs. This type of research uses a descriptive quantitative approach and the method used is purposive sampling technique by distributing questionnaires to 59 MSME employees in fishery processing with a minimum working period of 2 years. The results of this study are the more selection systems, the lower the employee's performance. The more selection systems, the lower the communication, but not significantly. The more training, the less communication. The more training, the significantly increased employee performance. The more communication, the significantly increased employee performance. The selection system has no significant effect on employee performance if it is mediated by communication. Training has no significant effect on employee performance if it is mediated by communication.